Desenvolvimento de método analítico para determinação de ácido salicílico em leite utilizando spot tests em papel e processamento de imagens digitais - Conrado, Josiele Aparecida Magalhães (2022)
Milk is a widely consumed product on a global scale and different practices of adulteration and fraud are reported. The addition of Salicylic Acid (SA) configures as adulteration because it is used to reduce the growth of microorganisms, resulting in the increased added value of milk. However, its excessive intake can cause gastrointestinal pathologies and even lead to death. Generally, official analytical methods are laborious, time-consuming, and expensive, which limits their use in routine analysis. As a result, the development of alternative analytical methods for milk analysis is of great relevance. This dissertation presents the development of a simple, fast, miniaturized, portable, and low-cost analytical method for the determination of salicylic acid in milk. The method was based on the formation of a colored complex after the reaction between the analyte and Fe(III) ions performed on filter paper. The quantification was performed by the technique of processing digital images in different types of milk. The developed method showed linearity of SA as a function of the ash scale parameter in concentration ranges from 100 to 1200 mg L-1 for standard solution of AS in ethanol, 100 to 1500 mg L-1 (R2 = 0.9908) for raw milk, 300 to 2000 mg L-1 (R2 = 0.9916) for skimmed milk, 500 to 2000 mg L-1 (R2 = 0.991) for powdered milk, 100 to 2000 mg L-1 (R2 = 0.9917) for whole milk, and 100 to 1500 mg L-1 (R2 = 0.9937) for zero lactose milk. The accuracy of the method was obtained by evaluating the percentage of recovery and values between 71 and 120% were obtained. The accuracy of the method was evaluated with the determination of SA in 12 samples of skimmed milk fortified with a concentration of 500 mg L-1 and showed a coefficient of variation of 0.7%. The milk samples submitted to the developed method were acquired in the local trade and raw milk was collected in the rural area of Iturama. The presence of SA was not detected in any of the samples evaluated. The evaluation of the analytical parameters obtained and the application in different milk samples resulted in a simple analytical method, miniaturized and without sample preparation for determination of SA in milk as a tool for identification of adulteration practices.